Positive and Healthy Living Program Manual Development for Young People Living With HIV at the Comprehensive Care Center at the Kenyatta National Hospital: An Open Pilot Implementation Trial - Machuka, Judy; Wambua, Grace Nduku; Musindo, Otsetswe; Bukusi, David; Okech, Violet; Muiruri, Peter; Maina, Rachel; Opiyo, Nelly; Ng'ang'a, Pauline; Kumar, Manasi (Frontiers in Psychiatry, 2020)
Background: Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) remains a great challenge among young people in Kenya. Young people living with HIV are faced with a lot of challenges that are often overlooked and may have an impact on their treatment adherence and overall well-being. This calls for interventions that are age-appropriate, and which tap into the psychosocial problems they experience. This is a protocol of a proposed study aimed at developing a facilitator-led peer support manual called ‘Positive and Healthy Living Program’ that will be the basis for running support groups with young people at the Comprehensive Care Centre at the Kenyatta National Hospital. Methods: We will carry out our study in two phases. The first phase will focus on the development of the manual and training of peer-facilitators. The second phase will make use of a pilot trial research design using both qualitative and quantitative approaches. It will be carried out among 10-24-year-old young people attending CCC at KNH; Tumaini Group (10-14years), Amani (15-19years) and Hodari Group (20-24years). The groups will participate in an 8-session support group, whose activities will focus on four domains namely: social-recreation, psychotherapy, peer-modelling and psychoeducation. Quantitative data will be collected using laboratory measures of Viral Load and CD4 as well as socio-psychological assessment tools. Qualitative data will be collected through interviews with the young people and peer facilitators. We will conduct a descriptive analysis which will describe the key features of the dataset and bivariate analyses will examine the association between variables. The change will be measured at baseline and post-treatment. The interviews will be coded into themes and we will generate experiential categories from the data around the effectiveness of the program, peer facilitators’ experience of providing support and how the young people respond to the program and its influence on their overall well-being. Discussion: We expect that the peer facilitators will find this manualized treatment acceptable and the 8-sessions group intervention will be feasible for the three age groups. We hypothesize that there will be improvements detected with regards to reported adherence and viral load, self-esteem, depression and psychological functioning.